2009
DOI: 10.1073/pnas.0903602106
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin-angiotensin system in autoimmune inflammation of the central nervous system

Abstract: Angiotensin II is the principle effector molecule of the renin angiotensin system (RAS). It exerts its various actions on the cardiovascular and renal system, mainly via interaction with the angiotensin II type-1 receptor (AT1R), which contributes to blood pressure regulation and development of hypertension but may also mediate effects on the immune system. Here we study the role of the RAS in myelinoligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis ( antigen presenting cell ͉ blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
134
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 32 publications
6
134
4
1
Order By: Relevance
“…In the present study, aliskiren attenuated the intense pro-inflammatory profile in retina of Ren-2 rats with diabetes or OIR, with a reduction in leucostasis, ICAM-1 production and ED-1 immunolabelling to control levels. There is evidence that aliskiren reduced the macrophage content of atherosclerotic plaques [30], leucocyte adhesion in femoral arteries [31] and the number of CD11b + and CD11c + antigen presenting cells in a model of multiple sclerosis [32]. The results of the present study are consistent with these findings, and highlight the potent anti-inflammatory properties of aliskiren.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, aliskiren attenuated the intense pro-inflammatory profile in retina of Ren-2 rats with diabetes or OIR, with a reduction in leucostasis, ICAM-1 production and ED-1 immunolabelling to control levels. There is evidence that aliskiren reduced the macrophage content of atherosclerotic plaques [30], leucocyte adhesion in femoral arteries [31] and the number of CD11b + and CD11c + antigen presenting cells in a model of multiple sclerosis [32]. The results of the present study are consistent with these findings, and highlight the potent anti-inflammatory properties of aliskiren.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, it has been shown that deletion of immune cells or immune suppression therapy reduces Ang II-dependent hypertension and hypertensive end organ damage, respectively (3,4). In line with these results, recent studies have provided profound evidence that AT1 receptor inhibition directly affects immune cell function and thereby ameliorates the clinical course of experimental autoimmune encephalomyelitis (EAE) (5,6) or systemic lupus erythematosus (7,8).…”
supporting
confidence: 59%
“…Several in vitro and in vivo studies have demonstrated that losartan inhibits DC activation (14,15,17). Elucidating the effects that losartan has on these factors may provide further insight into the pathology of inflammation, given that these factors are important in the development of LPS-induced ALI.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that Ang II could induce DCs maturation (14,17). Additionally, several lines of evidence demonstrate that Ang II induces Th1 and Th17 immune responses and ultimately enhances inflammation in several Ang II-mediated inflammatory diseases (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%